Interpreting sexist discourse in the European parliament: a case study - Bartłomiejczyk, Magdalena (Penerbit Universiti Kebangsaan Malaysia, 2023)
The paper employs critical discourse analysis for a pragmatically-oriented exploration of sexist statements by a Polish Eurosceptic Member of the European Parliament, Janusz Korwin-Mikke. Extracts from plenary speeches (delivered by the controversial politician between 2014 and 2018, originally in Polish or English) are compared with their interpretations into German and, respectively, either English or Polish. The qualitative analysis reveals a pronounced trend towards mitigation of sexist discourse by interpreters, particularly strong if the original sexism relied exclusively on the linguistic forms selected by the speaker. Impersonalization seems to be the most typical shift mitigating sexist remarks, other frequent shifts include addition of hedges and omission of evidentiality markers. Mitigation is understood here as a discursive shift in the interpreted text which does not necessarily result from the interpreter’s conscious decision. It may often occur as a side-effect of interpreting strategies used to overcome comprehension problems or to keep pace with the swift delivery of the original speaker. It is sometimes also attributable to systemic differences between the source and target languages. Sexism present in the source text appears to frequently contribute to serious problems with interpreting accuracy, diminishing the quality of the original argumentation in the interpretations.